Histologically low‐grade, yet biologically high‐grade, canine cutaneous mast cell tumours: A systematic review and meta‐analysis of individual participant data. (10th March 2020) - Bae, Sohee; Milovancev, Milan; Bartels, Courtney; Irvin, Veronica L.; Tuohy, Joanne L.; Townsend, Katy L.; Leeper, Haley
Abstract: Low‐grade canine cutaneous mast cell tumour (cMCT) with metastasis at the time of treatment is uncommonly reported, with few studies focusing on this specific clinical entity. The specific objective of this study was to systematically review the veterinary literature and perform a meta‐analysis summarizing the clinical presentation, treatments reported and clinical outcomes from dogs with histologically low‐grade cMCT and metastasis present at initial treatment. A total of 980 studies were screened with eight publications providing data on 121 dogs ultimately included. The most common treatments were surgery with adjuvant chemotherapy in 83/121 (69%) dogs; combined surgery, radiation and chemotherapy in 17/121 (14%) dogs; chemotherapy alone in 12/121 (10%) dogs and surgery alone in 7/121 (6%) dogs. Dogs with distant metastasis (n = 22) experienced significantly shorter survival compared with those with regional lymph node (RLN) metastasis (n = 99; median 194 vs 637 days; P  < .01). Two variables were significantly associated with increased risk of death: presence of distant (vs RLN) metastasis (hazard ratio = 2.60; P  < .01) and not receiving surgery as a component of treatment (hazard ratio = 3.79; P  < .01). Risk of bias was judged to be low in terms of selection and performance bias but high in terms of detection and exclusion bias. In conclusion, dogs with cMCT and RLN metastasis can be expected to live significantly longer than those with distant metastasis, and surgery appears to have a role in extending survival of metastatic low‐grade cMCT.